Preparation of Teucrium polium extract-loaded chitosan-sodium lauryl sulfate beads and chitosan-alginate films for wound dressing application - Mariem Kharroubi; Fatima Bellali; Abdelhafid Karrat; Mohamed Bouchdoug; Abderrahim Jaouad (AIMS Press, 2021)
This study aimed to formulate sodium lauryl sulfate cross-linked chitosan beads and sodium alginate-chitosan films for designing a dressing that would shorten the healing time of skin wounds. Teucrium polium extract-loaded chitosan-sodium lauryl sulfate beads (CH-SLS) and chitosan-alginate (CH-ALG) films were prepared and characterized by using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) analysis, and scanning electron microscopy (SEM). The swelling properties of the CH-SLS beads were also analyzed in a water solution. The obtained Teucrium polium extract-loaded CH-SLS beads and CH-ALG films (TBF) were further incorporated into the commercial adhesive dressing. This TBF wound dressing was then investigated for evaluation of its wound healing potential in the mice using the excision wound model. Healing was assessed by the macroscopic appearance and the rate of wound contraction during 8 days. On day 4, the TBF-treated wounds exhibited 98% reduction in the wound area when they were compared with healing ointment, elastic adhesive dressing, and untreated wounds which were exhibited 63%, 43%, and 32%, respectively. Furthermore, the application of TBF dressing reduced skin wound rank scores and increased the percentage of wounds contraction. These results demonstrate that TBF dressing improves considerably the healing rate and the macroscopic wound appearance at a short delay and this application may have therapeutic benefits in wound healing.